The significant role of IL-15, IL-22, IL-37, and caspase 9 in polycystic ovary syndrome: A case-control study in a sample of Iraqi women - Noor A. Mohammed; Ghassan M. Sulaiman; Hazima M. Alabassi; Khalil A.A. Khalil; Elsadig M. Ahmed (Journal of Genetic Engineering and Biotechnology)
The study aims to evaluate the significant role of interleukin 15 (IL-15), IL-22, IL-37, and Caspase 9 gene expression in polycystic ovary syndrome (PCOS), focusing on the underlying mechanisms and potential diagnostic or therapeutic implications. Peripheral blood has been collected, and serum was separated for the evaluation of the serum IL-15, IL-22, and IL-37. The ELISA technique has been carried out to determine the serum levels of understudied factors mentioned above in Iraqi women patients diagnosed with PCOS (No. = 90) via a specialized gynecologist and healthy fertile women (No. = 48) as a control group. In addition, a genetic study on the expression of the caspase 9 gene in these patients had been performed. The data reveals statistically significant differences in interleukin levels in PCOS patients versus the control group. Specifically, the PCOS group exhibits significantly higher levels of IL-15 and IL-22 as compared to the control group. Conversely, the PCOS group shows significantly lower levels of IL-37 compared to the control group. The results showed no statistically significant difference in the mean expression of the Caspase 9 gene when comparing these fold graduations. However, it’s worth noting that a higher fold frequency was observed in both the PCOS and control groups, with 57.1 % and 60 %, respectively, having folds less than 1. The distribution of folds varied across other categories was also addressed. Additionally, there was a notable difference in the frequency of 11.4 % in the PCOS group compared to 2 % in the control group for folds greater than 9. The findings suggest that interleukins, particularly IL-22 and IL-37, hold promise as diagnostic markers for distinguishing PCOS from healthy conditions. However, the potential diagnostic utility of the Caspase 9 gene expression was not confirmed in this study.